Evaluation of mycobacterium smegmatis infected d THP-1 macrophages as a model to assess host directed therapy: using apoptotic agents as repurposed anti-tuberculosis drug leads. - Ymele Soko, Vivette (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.